2019
DOI: 10.1088/1748-9326/ab1def
|View full text |Cite
|
Sign up to set email alerts
|

Strong seedling recruitment does not limit mangrove vulnerability to harvest

Abstract: Ecological studies on the impacts of timber harvesting contributed to inform sustainable management strategies of tropical forests. However, these studies rely strongly on two major assumptions: (i) strong seedlings recruitment predispose for positive population dynamics, and (ii) more adult trees is a guarantee for a strong reproductive capability of the population. These assumptions are applied without accounting for the life history of the harvested species. Here, we revisit these assumptions in light of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 67 publications
(83 reference statements)
0
7
0
Order By: Relevance
“…The number of seedlings in this area was greater than other studies in a threatened protected forest in South Sumatra ranged from 100-800 seedling/ha [37]. The high number of recruitments in mangrove forests has indicated that the forest was IOP Publishing doi:10.1088/1755-1315/944/1/012017 5 in stable condition, while it was still limited to harvest mangrove wood [38]. Sapling stand-level had a gradually increasing trend from landward to seaward zone, at 200 to 400 sapling/ha, respectively.…”
Section: Mangrove Community Structurementioning
confidence: 62%
“…The number of seedlings in this area was greater than other studies in a threatened protected forest in South Sumatra ranged from 100-800 seedling/ha [37]. The high number of recruitments in mangrove forests has indicated that the forest was IOP Publishing doi:10.1088/1755-1315/944/1/012017 5 in stable condition, while it was still limited to harvest mangrove wood [38]. Sapling stand-level had a gradually increasing trend from landward to seaward zone, at 200 to 400 sapling/ha, respectively.…”
Section: Mangrove Community Structurementioning
confidence: 62%
“…The reason is that the traditional belief in the reverse J-growth trajectory as indicative of positive growth does not take into consideration the life history of the species at hand. Such consideration is critical since long-and shortlived species respond differently to perturbations ( [64]; see also Gaoue and Yessoufou [65]). This is because long-lived species, unlike short-lived ones, invest heavily in long-term survival strategies [66].…”
Section: Discussionmentioning
confidence: 99%
“…This is because long-lived species, unlike short-lived ones, invest heavily in long-term survival strategies [66]. According to life history theory, the survival of reproductive adults drives long-term population growth for long-lived species [64,65,67,68]. As such, low proportions of early life stages, such as those we found in the present study for a long-lived species like E. lanatus, would have limited impacts on the long-term population dynamics of this cycad species (see [65]).…”
Section: Discussionmentioning
confidence: 99%
“…Mangrove species breed repeatedly, and trees from different generations form part of the structure of the forest, yet recruitment alone is not enough to maintain or regenerate a mangrove forest because mortality from size class I to size class II was large at all the observed areas. Climate extremes (cold and warm) and herbivory contribute to seedling mortality [50,51] and the loss at smaller size classes has a strong influence on larger classes [52]. Larger trees suffer senescence and contribute less to recruits, thus conserving larger trees while harvesting relatively young trees was not a good management practice [53].…”
Section: Discussionmentioning
confidence: 99%